1988
DOI: 10.1002/anie.198811641
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of η1‐Nitrosyl to η2‐Hydroxylaminyl Ligands in the Reduction of [Mo(NO)2(‘S4’)] to [Mo(η2‐NH2O)(NO)(‘S4’)]: A Model Reaction for a Partial Step in the Enzymatic NO→NH3 Conversion

Abstract: We thank a referee for bringing to our attention recent publications on other systematic investigations on the large effect of changes on hostguest complexes: a) F. Diederich, Angew. Chem. 100 (1988) 372 (especially p. 382); Angew. Chem. Int. Ed. Engl. 27 (1988) 362; b) T. J. Shepodd, M. A. Petti, D. A. Dougherty, J. Am. Chem. Soc llO(1988) 1983. 131 All new compounds gave satisfactory analytical data ( ' H and ''C NMR, elemental analyses) [4] H.-J. Schneider, R. Kramer, J. Pdhlmann, U. Schneider, J . Am. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…When the reaction conditions were altered from air to a nitrogen atmosphere at a lower temperature, product 13 could be isolated in an increased yield of 72% (Figure b). The X-ray crystal structure analysis of compound 13a with a BF 4 counteranion revealed that the chloride ligand on the osmium center had been replaced by a three-electron donor hydroxylamido (NH 2 O) ligand, adopting an η 2 -N,O coordination mode . Subsequently, heating a methanol solution of compound 13 under an air atmosphere resulted in its nearly complete conversion to compound 5 through the oxidation of the NH 2 O moiety to NO, thereby demonstrating the role of the reaction intermediate of the osmium hydroxylamido complex.…”
Section: Resultsmentioning
confidence: 99%
“…When the reaction conditions were altered from air to a nitrogen atmosphere at a lower temperature, product 13 could be isolated in an increased yield of 72% (Figure b). The X-ray crystal structure analysis of compound 13a with a BF 4 counteranion revealed that the chloride ligand on the osmium center had been replaced by a three-electron donor hydroxylamido (NH 2 O) ligand, adopting an η 2 -N,O coordination mode . Subsequently, heating a methanol solution of compound 13 under an air atmosphere resulted in its nearly complete conversion to compound 5 through the oxidation of the NH 2 O moiety to NO, thereby demonstrating the role of the reaction intermediate of the osmium hydroxylamido complex.…”
Section: Resultsmentioning
confidence: 99%